Post-irradiation helium blistering in copper, austenitic steels and alloys over the temperature interval 0.65-0.95Tmelt - Kadyrov, H.G.; Tsai, K.V. (Вопросы атомной науки и техники, 2000)
The specimens of copper, austenitic steel 08Cr16Ni15Mo3Nb and nickel-rich 03Cr20Ni45 alloys were irradiated by a-particles (50 MeV, 0.3...3.6 × 10²¹m⁻²) through the special filter-mask and subjected to following thermal treatment at temperatures up to 0.95 × Tmelt for 1...100 h . The helium behavior in the materials was investigated by the methods of scanning electron microscopy and profilimetry of a surface. It was shown that the development of helium bubbles in a closed bulk of the specimens during high-temperature annealing leads to appearing steps on irradiated surfaces followed by flacks and blisters. Migration of helium bubbles in the field of stress gradients causes the nucleation and growth of the long-distance gas-filled cracks. Accumulation of helium bubbles in the cracks leads to lifting of surface layers and formation of a dome-shaped step on the irradiated surface, i.e. the bulk blistering occurs.